G281(P) The Norfolk Paediatric Education Group (NPEG): a high quality, multiprofessional, multicentre learning environment in a rural area. (7th April 2014) - Brightwell, A; Gallagher, K; Datta, V
Abstract : Introduction/aim: Norfolk is a rural county in the East of England with large distances between hospitals and no motorways. The Norfolk Paediatric Education Group (NPEG) was established in 2007 with the aim of overcoming these challenges by providing high quality, multi-professional, networked teaching across the region. Teaching is provided by video-link between four hospitals on a monthly basis and is accredited for CPD points by the RCPCH. We aimed to demonstrate the effectiveness of NPEG as a multiprofessional learning resource. Methods: We evaluated the effectiveness of NPEG by means of an online survey and review of feedback between 2010 and 2013. A modified thematic framework analysis was used to interpret freetext responses. Results: 768 feedback forms were reviewed from three centres. 93% of sessions were rated as good or excellent. The breakdown of attendee by profession was: 38% (296) were consultants or career grade paediatricians, 35% (270) paediatric trainees and foundation doctors, 8% (60) medical students, 4% (29) specialist nurses, 6% (45) allied health professionals, 6% (44) nurses and 3% (24) others including commissioners and chaplaincy staff. When asked in the online survey, "What is the most valuable aspect of NPEG?" emerging themes included high quality, multi-centre, multi-professional teaching, ease of access and networking. Respondents felt that compared to other forms of teaching/CPD, NPEG was advantageous in terms of ease of access, the high quality of sessions and that it provided unique opportunities to learn from other centres and other professionals in the region. In particular, the opportunity to regularly access teaching onsite that would otherwise have required considerable time and expense was highly valued by participants. Conclusion: NPEG is a well established innovative educational resource providing a high quality teaching-learning environment in a rural setting. NPEG is regularly attended by professionals from across the entire multidisciplinary team and is highly rated by participants. By reducing travel time and disruption to local service, NPEG provides a sustainable and green model for regional network teaching which can be adapted to other regions.